Subduction-obduction related petrogenetic and metamorphic evolution of the Semail ophiolite sole in Oman and the United Arab Emirates - Cox, J; Jon S. Cox (2000)
Structural field observations, combined with petrological, isotopic and geochemical analysis of metamorphic and igneous rocks associated with the Semail ophiolite of Oman and the United Arab Emirates, have been used in conjunction with geochronology and estimates of metamorphic conditions and PT paths to constrain the ophiolite emplacement history. The ophiolite metamorphic sole was formed at peak conditions of 840 ± 70°C and 11.6 ± 1.6 kbar (THERMOCALC) and 840-870°C and 11.8-13.9 kbar (conventional thermobarometry) and is characterised by an anticlockwise PTt path. Further analysis and structural constraints imply an apparent inverted sole gradient of ~2°C m-1 and ~3.7 MPa m-1. In conjunction with existing geochronology, a peak sole exhumation rate of ~12.5 mm yr-1 is indicated. Geochemical analysis and tectonic constraints suggest that the Semail ophiolite sole formed from neo Tethyan MORB crust similar in composition to the preserved Triassic-Jurassic Haybi tholeiites and Masirah ophiolite crust. The Bani Hamid granulite facies sole metamorphism peaked at ~96.5 Ma and exhibits a similar PTt path and peak conditions, but formed from oceanic island igneous, volcanoclastic and sedimentary protoliths. Anatectic granitoids in the ophiolite mantle sequence have geochemical and isotopic (Rb-Sr and Sm-Nd) characteristics compatible with derivation from the Bani Hamid sole granulites during prograde metamorphism and have ages of 98.8 ± 9.5 Ma, 93.0 ± 10.0 Ma (Sm- Nd) and 105 ± 4 Ma (U-Pb). The Saih Hatat high pressure metamorphic terrane beneath the ophiolite consists of two contrasting structural levels juxtaposed during exhumation following the subduction of the Arabian continental margin beneath the advancing ophiolite. PT analysis shows the HP event culminated at 450-550°C and 20.0 ± 1.5 kbar (THERMOCALC) and was characterised by a clockwise PTt path. In conjunction with ambiguous existing geochronology, a peak exhumation rate of ~4-12 mm yr-1 is indicated, followed by erosion at ~0.5 mm yr-1.